A robust ultra-broad-band wireless communication system using SAW chirped delay lines - Springer, Andreas; Weigel, Robert; Pohl, Alfred; Gugler, Wolfgang; Huemer, Mario; Reindl, Leonhard; Ruppel, Clemens; Seifert, Franz (IEEE Transactions on Microwave Theory and Techniques, 1998)
Design and performance of a low-cost wireless communication system for indoor and industrial environments are presented. The system is based on chirp-signal transmission to achieve a robust communication link. For the chirp expansion and compression, surface acoustic wave chirped delay lines fabricated from LiTaO3-X112rotY are used. Center frequency, bandwidth, and chirp rate are 348.8 MHz, 80 MHz, and ±40 MHz/μs, respectively. An optimized square-root weighting was chosen to reduce the sidelobes of the compressed pulse to -42 dB compared to the correlation peak. The chirp filters have been deployed in a hardware demonstrator for data rates of up to 5 Mb/s. Limiting factors for the data rate according to simulations and measurements are mainly intersymbol interferences due to the time overlapping of consecutive symbols and, to a lower extent, the multipath propagation
elib2cris::1512001600,springer1998d